ANALISA POSITIONING SUPERMARKET (LOTTEMART,SUPERINDO,TIPTOP,CARREFOUR,GIANT) BERDASARKAN ATRIBUT YANG DIPERSEPSIKAN OLEH KONSUMEN - SUHA RINI RINI (Universitas Bina Sarana Informatika, 2017)
Of course everyone has different experiences and perceptions in terms of shopping at the supermarket, and it can be used as a tool to find out how consumers' assessment of the attributes of the supermarket which include: location, products, services salesperson, cashier, the price of goods, discount, direct gifts, cleanliness, air conditioning, free parking. After knowing what consumers' assessment of their attributes can be further analyzed how the